Measurement of Bs0 mixing parameters from the flavor-tagged decay Bs0-->J/psiphi. - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Aguilo, E; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; Alton, A; et al. (2008)
From an analysis of the flavor-tagged decay Bs0-->J/psiphi we obtain the width difference between the Bs0 light and heavy mass eigenstates, DeltaGammas = 0.19+/-0.07(stat)(-0.01)+0.02(syst) ps(-1), and the CP-violating phase, phi s= -0.57(-0.30)+0.24(stat)(-0.02)+0.08(syst). The allowed 90% CL intervals of DeltaGammas and phi s are 0.06 < DeltaGammas < 0.30 ps(-1) and -1.20 < phi s < 0.06, respectively. The data sample corresponds to an integrated luminosity of 2.8 fb(-1) accumulated with the D0 detector at the Fermilab Tevatron collider.